Covalent Mucin Coatings Form Stable Anti‐Biofouling Layers on a Broad Range of Medical Polymer Materials. Issue 4 (20th January 2020) - Winkeljann, Benjamin; Bauer, Maria G.; Marczynski, Matthias; Rauh, Theresa; Sieber, Stephan A.; Lieleg, Oliver
Abstract: Approximately 10% of all hospital patients contract infections from temporary clinical implants such as urinal and vascular catheters or tracheal tubes. The ensuing complications reach from patient inconvenience and tissue inflammation to severe, life threatening complications such as pneumonia or bacteremia. All these device‐associated nosocomial infections have the same origin: biofouling, i.e., the unwanted deposition of proteins, bacteria, and cells onto the device. To date, most strategies to overcome these problems are device specific, which results in high development efforts and costs. Here, it is demonstrated how one and the same coupling mechanism can be used to create a covalent antifouling coating employing mucin glycoproteins on multiple materials: with this method, a stable mucin layer can be generated on a broad range of polymer materials which are frequently used in medical engineering. It is shown that the mucin coating exhibits excellent stability against mechanical, thermal, and chemical challenges and reduces protein adsorption as well as prokaryotic and eukaryotic cell adhesion. Thus, the coating mechanism described here introduces a promising strategy to overcome biofouling issues on a broad range of medical devices. Abstract : The covalent coating strategy introduced here is based on a two‐step coupling process, can be applied to a broad range of medically relevant polymer materials and produces mucin layers, which resist mechanical and chemical challenges. The anti‐biofouling properties of those mucin coatings combine reduced protein adsorption as well as decreased prokaryotic and eukaryotic cell adhesion.